JWST Near-infrared Spectroscopy of High-albedo Jupiter Trojans: A New Surface Type in the Trojan Belt - Michael E. Brown; Ian Wong; Matthew Belyakov (The Planetary Science Journal)
We present 0.8–5 μ m JWST spectra of four  ~20 km diameter Jupiter Trojans known to have albedos elevated above the values typical in the remaining Trojan population. The spectra of these four high-albedo Jupiter Trojans are all similar, with red slopes in the optical–IR transition region, a break to lower slopes at 1.3 μ m, and a broad absorptions from 2.8 to 4 μ m. The 0.8–2.5 μ m spectra of these objects match the spectra of neither the well-known “red” and “less-red” Jupiter Trojans nor of any known asteroid taxonomic class. The reflectivity of these objects does not rise redward of 4 μ m, a property that is seen in the previous JWST observations of Jupiter Trojans only in Polymele. Indeed, the high-albedo Jupiter Trojan spectra are a good match to that of Polymele, and Polymele is both the smallest Jupiter Trojan in the previous JWST sample and has the highest albedo of the objects in that sample. We conclude that Polymele and the other high-albedo Jupiter Trojans represent a third class of Jupiter Trojans not represented in the more heavily studied larger objects and are perhaps the products of recent disruptions. The Lucy flyby of Polymele in 2027 September will give a direct view of one of this new class of Jupiter Trojans.